MADHOUSE AND THE WHOLE THING THERE: AUTHENTICITY, AUTOETHNOGRAPHY AND PSYCHIATRY - Clarke, Simon P. (2020)
This thesis has been concerned with the question of authenticity in relation to autoethnographic mad narratives. Emerging from the ‘narrative crisis’ in the social sciences, autoethnography is a methodology that utilises personal experience (‘auto’) in the observation and analysis of social phenomenon (‘ethnography’). Along with other forms of first-person accounts of madness, autoethnography can arguably provide useful insights into the subjective experience of going mad and using mental health services, whilst also providing critiques of biomedical psychiatry. However, many of these accounts are predicated on an argument from authenticity, even when using theoretical frameworks that repudiate any notion of a true self. In this thesis, I thus analysed the concept of authenticity in relation to mad narratives, arguing for a redeployment of the concept using De Certeau’s (1984) distinction between ‘strategy’ and ‘tactics’. In doing so, I argued that a ‘tactically authentic’ autoethnography would be a narrative that incorporated multiple perspectives, be ambitious in its textual representation, be systematic in in its analysis of the data, and relate the narrative to social theory. Following mental health and survivor research, I also argued that a tactically authentic account of madness would also incorporate critiques and analysis of the psychiatric system. Therefore, in responding to these critiques of autoethnography, and to address the main thesis questions, an innovative autoethnographic methodology was developed, called a ‘quadrilogue’. This method incorporated four perspectives in recounting my psychotic breakdown and psychiatric hospitalisation that occurred in the early 1990s. The four perspectives were: mine; my mother’s, represented by her diary that she kept at the time; the clinical team, as represented in my NHS clinical notes; and the reflexive perspective from the researcher, compiled from my own and others’ reflections on the data. Analysis of the data generated three main themes. The first of these, double binds, using Bateson’s (1972) Double Bind theory to show the transcontexual ways in which the psychiatric system inflicted double binds on me, my family and staff. The second theme, mis/recognition, argued that the discourse of psychiatry itself was constituted in a ‘differend’ (Lyotard, 1983) that prevented me, and to a lesser extent my mother, from adequately framing our complaints. The third, despair, argued that despair is unrepresented in the psychiatric research literature, despite being present in first-person accounts, and was a key aspect of my experience in the narrative. However, this ‘despair’ was marginalised by the psychiatric system in the narrative, and lacks an adequate conceptual framing in the literature based on service user and survivor experiences. There were at least two key contributions to the literature. The first was that in developing the quadrilogue, I had constructed a methodology that addressed issues in the literature and could be used to inform future autoethnographic research. The second was in the generation of new theories, as well as the adaptations of existing theory, grounded in the experiences of those who have use, or have used, mental health services.